AB1285 IGA RF IS ASSOCIATED WITH HIGH AGE OF RHEUMATOID ARTHRITIS ONSET. (June 2019) - Pertsinidou, Eleftheria; Klareskog, Lars; Alfredsson, Lars; Mathsson, Linda; Hansson, Monika; Westerlind, Helga; Askling, Johan; Saevarsdottir, Saedis; Rönnelid, Johan
Abstract : Background: IgM RF and anti-CCP2 have been shown to associate with young age at RA diagnosis [1, 2]. By contrast, little is known about the association between other RF isotypes and age at onset, or sex. Objectives: To examine the association between individual RA autoantibodies, sex and age at RA onset. Methods: Anti-CCP2, IgA-, IgG- and IgM-RF were analysed centrally in baseline sera from 1600 Epidemiological Investigations in RA (EIRA) patients aged 18-70 years and classified according to the 1987 ACR criteria within one year of first symptoms. Cut-offs for RF isotypes were determined at the 98 th percentile based on the EIRA RA-free controls, close to the 98.4% anti-CCP2 specificity. Results: Anti-CCP2, IgA-, IgG- and IgM RF were found in 1020 (64%), 692 (43%), 529 (33%), and 916 (57%), of the patients, respectively. Mean (median) age at diagnosis among men was 54 (57) year, higher than 51 (54) years among women (p<0.0001). The figure shows the autoantibody distribution in relation to sex and age tertiles. In univariate analysis, anti-CCP2 and IgM RF were both associated with lower age at RA diagnosis (table). When occurrence of all four autoantibodies were compared simultaneously as independent variables and with age at diagnosis as dependent variable in multiple regression, a strong association between IgA RF and higher age at RA diagnosis appeared, and the association between IgM RF and low age at RA diagnosis weakened (table). IgA RF and IgG RF associated with male sex, but IgM RF with female sex. No sex-difference was seen for anti-CCP2 (table). When the multiple regression was adjusted for sex, the association between IgM RF and age disappeared, whereas the strong associations between IgA RF and high age and between anti-CCP2 and low age at diagnosis persisted (table). Conclusion: On average, IgA RF positive (vs. negative) RA patients are almost four years older at the time of diagnosis; the opposite was found for anti-CCP2 and IgM RF. Whereas sex-differences explain the age-association for IgM RF, this is not the case for anti-CCP2 and for IgA RF. References: [1] Diaz FJ, et al. Joint Bone Spine 2011;78:175. [2] Jacobsen S. Clin Rheumatol 2004;23:121. Disclosure of Interests: Eleftheria Pertsinidou: None declared, Lars Klareskog Grant/research support from: Yes, but not for the presented study., Lars Alfredsson: None declared, Linda Mathsson Employee of: employed by Thermo Fisher Scientific, Monika Hansson: None declared, Helga Westerlind: None declared, Johan Askling Grant/research support from: Karolinska Institutet (JA) has or has had research agreements with the following pharmaceutical companies, mainly in the context of the ATRIS national safety monitoring programme for rheumatology biologicals: Abbvie, BMS, MSD, Eli Lilly, Pfizer, Roche, Samsung Bioepis, and UCB., Consultant for: Karolinska Institutet has received remuneration for JA participating in ad boards arranged by Lilly, Novartis, and Pfizer., Saedis Saevarsdottir Employee of: Part-time employee at deCODE Genetics/Amgen Inc, working on genetic research unrelated to this project., Johan Rönnelid: none declared